2017
DOI: 10.1186/s12955-017-0685-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation for patients with lower extremity sarcoma: application of the Chinese version of Musculoskeletal Tumor Society scoring system

Abstract: BackgroundThe Musculoskeletal Tumor Society (MSTS) scoring system is a disease-specific instrument to determine the physical and mental health for patients with extremity sarcoma. This study aims to investigate the reliability and validity of the Chinese version of the MSTS, and to evaluate functional outcomes of the surgical treatment of lower extremity sarcoma using the Chinese MSTS.MethodsA cohort of 98 patients who had undergone surgery for lower extremity sarcoma were included. All the patients completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
4
23
0
Order By: Relevance
“…The good internal consistency found in this study is however comparable to those found by Rebolledo et al[7], Xu et al[9] and Iwata et al[8]. The inter-rater reliability also showed excellent results for both versions, and is in accordance with those found by Rebolledo et al[7] and Xu et al[9]. The original validation of the MSTS questionnaire also reported good inter-observer reliability, although no correlation coefficient was reported[1].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The good internal consistency found in this study is however comparable to those found by Rebolledo et al[7], Xu et al[9] and Iwata et al[8]. The inter-rater reliability also showed excellent results for both versions, and is in accordance with those found by Rebolledo et al[7] and Xu et al[9]. The original validation of the MSTS questionnaire also reported good inter-observer reliability, although no correlation coefficient was reported[1].…”
Section: Discussionsupporting
confidence: 91%
“…The original validation of the English version of the MSTS unfortunately did not report a Cronbach’s α[1]. The good internal consistency found in this study is however comparable to those found by Rebolledo et al[7], Xu et al[9] and Iwata et al[8]. The inter-rater reliability also showed excellent results for both versions, and is in accordance with those found by Rebolledo et al[7] and Xu et al[9].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations